1995
DOI: 10.1093/infdis/172.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anti-Influenza A Virus Cytotoxic T Cell Activity following Vaccination of the Chronically III Elderly with Live Attenuated or Inactivated Influenza Virus Vaccine

Abstract: The possible enhancement of anti-influenza A virus memory cytotoxic T cell (CTL) responses to inactivated influenza virus vaccine by coadministration of intranasal live attenuated influenza A virus vaccine was investigated. Fifty elderly nursing home residents received inactivated trivalent influenza virus vaccine intramuscularly and simultaneously were randomly assigned to receive either bivalent live attenuated influenza A virus vaccine or saline placebo intranasally in a blinded fashion. A larger proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…He et al reported that the frequency of influenza A virusspecific IFN-␥-producing CD4 and CD8 T cells significantly increased after LAIV but not TIV immunization in children of ages 5 to 9 years (26). A larger proportion of elderly volunteers who received both LAIV and TIV than of those who received TIV alone experienced a postvaccination rise in anti-influenza A virus CTL activity (22). These studies suggest that LAIV might have more benefits than TIV in providing cross-protection against variant influenza viruses, and this needs to be further confirmed by a well-designed case-control study in the future.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 99%
“…He et al reported that the frequency of influenza A virusspecific IFN-␥-producing CD4 and CD8 T cells significantly increased after LAIV but not TIV immunization in children of ages 5 to 9 years (26). A larger proportion of elderly volunteers who received both LAIV and TIV than of those who received TIV alone experienced a postvaccination rise in anti-influenza A virus CTL activity (22). These studies suggest that LAIV might have more benefits than TIV in providing cross-protection against variant influenza viruses, and this needs to be further confirmed by a well-designed case-control study in the future.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 99%
“…On the contrary, protective immunity induced by most inactivated influenza vaccines (IIV) has been correlated with antibodies directed to virion-expressed hemagglutinin (HA) (6)(7)(8). Finally, protection induced by live-attenuated influenza vaccines (LAIV) is not as well established but appears to correlate with several immune mechanisms, including cellular and mucosal immunity (3,(9)(10)(11), resulting in high level of heterosubtypic protection (12). Both IIV and LAIV require largescale production of infectious virus, and the process of cultivation of the vaccine antigens in eggs (the source of the vast majority of vaccine) often alters the antigenic structure of the resulting vaccine.…”
mentioning
confidence: 99%
“…First, live vaccines are thought to induce improved cross-reactive cell-mediated cytotoxicity as well as a humoral antibody response, providing better protection than inactivated vaccines (6,7). Second, protective immunity to equine influenza is likely to involve a mucosal immunoglobulin A (IgA) response which is not seen with traditional intramuscularly administered vaccines (19).…”
mentioning
confidence: 99%